2020
DOI: 10.1371/journal.pone.0226817
|View full text |Cite
|
Sign up to set email alerts
|

PCR for the detection of pathogens in neonatal early onset sepsis

Abstract: Background A large proportion of neonates are treated for presumed bacterial sepsis with broad spectrum antibiotics even though their blood cultures subsequently show no growth. This study aimed to investigate PCR-based methods to identify pathogens not detected by conventional culture. Methods Whole blood samples of 208 neonates with suspected early onset sepsis were tested using a panel of multiplexed bacterial PCRs targeting Streptococcus pneumoniae, Streptococcus agalactiae (GBS), Staphylococcus aureus, St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 47 publications
1
27
1
1
Order By: Relevance
“…are the most important preventable causes of female infertility and adverse pregnancy outcomes [31]. Due to significant maternal colonization or infection, and subsequent fetal transmission, a growing body of evidence supports pre-natal diagnosis (preferably by a NAAT methodology) and treatment of these microbes [32] [33] We found that detection of polymicrobial infections (3 or more pathogens) in the urine samples of the pregnant population was significantly higher than the overall detection rate ( Figure 4). A recent study of symptomatic UTI patients demonstrated that multiplex PCR was able to detect the presence of pathogenic agents in 36% of concurrent, parallel "split samples", that tested negative with traditional culture techniques [34].…”
Section: Resultsmentioning
confidence: 76%
“…are the most important preventable causes of female infertility and adverse pregnancy outcomes [31]. Due to significant maternal colonization or infection, and subsequent fetal transmission, a growing body of evidence supports pre-natal diagnosis (preferably by a NAAT methodology) and treatment of these microbes [32] [33] We found that detection of polymicrobial infections (3 or more pathogens) in the urine samples of the pregnant population was significantly higher than the overall detection rate ( Figure 4). A recent study of symptomatic UTI patients demonstrated that multiplex PCR was able to detect the presence of pathogenic agents in 36% of concurrent, parallel "split samples", that tested negative with traditional culture techniques [34].…”
Section: Resultsmentioning
confidence: 76%
“…Tachypnoea is the most common presenting sign of EOGBS, with or without grunting, recession or nasal flaring, and may be very subtle. Hypothermia is a more common presentation than fever [13].…”
Section: Neonatal Infectionincidencementioning
confidence: 99%
“…The advantage of PCR is that a result can be obtained rapidly, and may detect other pathogens, leading to improved targeting of antibiotic therapy. A 2017 Cochrane review [65] and a 2020 study [13] suggest that PCR has the potential to be a highly valuable additional tool for the diagnosis of infection, including in those babies where conventional cultures were negative.…”
Section: Neonatal Managementmentioning
confidence: 99%
“…Recently, the PCR technique has been universal deployed in clinical diagnoses, which makes it possible to diagnose infectious diseases caused by microorganisms quickly and accurately. Moreover, numerous studies have shown that 16S rRNA PCR can diagnose neonatal sepsis [12][13][14][15][16][17]. The 16S rRNA gene is 1500 nucleotides long and encodes the 30S ribosomal subunit in all prokaryotes.…”
Section: Introductionmentioning
confidence: 99%